Crosstalk between circRNAs and the PI3K/AKT signaling pathway in cancer progression - Xue, Chen; Li, Ganglei; Lu, Juan; Li, Lanjuan (Signal transduction and targeted therapy, 2021)
Circular RNAs (circRNAs), covalently closed noncoding RNAs, are widely expressed in eukaryotes and viruses. They can function by regulating target gene expression, linear RNA transcription and protein generation. The phosphoinositide 3-kinase (PI3K)/AKT signaling pathway plays key roles in many biological and cellular processes, such as cell proliferation, growth, invasion, migration, and angiogenesis. It also plays a pivotal role in cancer progression. Emerging data suggest that the circRNA/PI3K/AKT axis modulates the expression of cancer-associated genes and thus regulates tumor progression. Aberrant regulation of the expression of circRNAs in the circRNA/PI3K/AKT axis is significantly associated with clinicopathological characteristics and plays an important role in the regulation of biological functions. In this review, we summarized the expression and biological functions of PI3K-AKT-related circRNAs in vitro and in vivo and assessed their associations with clinicopathological characteristics. We also further discussed the important role of circRNAs in the diagnosis, prognostication, and treatment of cancers.